The water tap design for ablution activities considering cultural influences: a design for sustainability - Ghazali, Ihwan; Padzil, Nur Wardah Sufina; Mohamad, Effendi Bin; Al-Mashjari, Layla Ahmed; Irianto, Irianto; Herawan, Safarudin Gazali (Frontiers in Environmental Science, 2023)
Water is a vital resource that should be utilized effectively. However, it is overused and squandered on a daily need, including the unrestrained use of water for ablution purposes. This condition can be due to a lack of awareness and the influences of peer cultural values. Therefore, the aim of this study is to develop a water-tap design that takes into consideration the influences of cultural value. Accordingly, confirmatory factor analysis and structural equation modelling (SEM) approach the significant correlation between cultural influences and user preferences on water-tap design by referring at the critical threshold output of each attribute. The result showed that collectivism and uncertainty avoidance dimensions were identified as the influencing cultural dimensions and the automatic water level-control float valve, mechanical water-taps with auto-stop function, and transparent water tanks are the most important considerations for water tap technical specification. Through the assessment of its applicability, the use of the prototype can reduce water usage by 54.6% compared to regular water-taps. Correspondingly, the approach of cultural value in the designing process is expected to give more insights to practices such as product designers when determining design specification while for knowledge, it extends the applicability of Hofstede cultural theory for product design and development.